2010
DOI: 10.1002/art.27308
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fetuses in a study of intravenous immunoglobulin as preventive therapy for congenital heart block: Results of a multicenter, prospective, open‐label clinical trial

Abstract: Objective The recurrence rate of anti-SSA/Ro associated congenital heart block (CHB) is 17%. Reversal of 3rd degree block has never been achieved. Based on potential reduction of maternal autoantibody titers as well as fetal inflammatory responses, IVIG was evaluated as a preventative therapy for CHB. Methods A multicenter open-label study based on Simon’s 2-stage optimal design was initiated. Enrollment criteria included: maternal anti-SSA/Ro antibody, a previous child with CHB/rash, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(136 citation statements)
references
References 35 publications
2
126
0
4
Order By: Relevance
“…immunoglobulins are not beneficial for preventing progression to congenital AVB. 33, 34 Similarly, the present study found a lack of superiority of transplacental treatment for second-degree AVB with bradyarrhythmia.…”
Section: Prevention Of Progression To Congenital Cavbsupporting
confidence: 44%
“…immunoglobulins are not beneficial for preventing progression to congenital AVB. 33, 34 Similarly, the present study found a lack of superiority of transplacental treatment for second-degree AVB with bradyarrhythmia.…”
Section: Prevention Of Progression To Congenital Cavbsupporting
confidence: 44%
“…15 Friedman et al documented cure of second-degree atrioventricular block in two of six fetuses treated with corticosteroids, but in spite of this treatment, three of the fetuses (50%) progressed to complete atrioventricular block (one intrauterine, two after delivery). 19 The incidence of fetal atrioventricular block is about 2% of pregnancies in females with SSA/ Ro or SSB/La autoantibodies. 18 Serial echocardiography screening is not helpful because there has been no evidence that this prevented the development of atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of recurrent atrioventricular block when a previous fetus has been affected is about 19%. 19 The most serious complication seen in females with positive antibodies is the occurrence of repolarization abnormalities and this may increase the incidence of sudden cardiac arrest documented in this group of patients. 20 In a females with SSA/Ro-related fetal cardiac complications, follow-up with FMCG is highly recommended to assess depolarization and repolarization anomalies, confirm the degree of block, and evaluate myocardial hypertrophy 21,22 but, this method is still not readily accessible to doctors in most centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Приблизительно у 1-3% плодов и новорожденных от матерей, позитивных по Ro/SSA-и La/SSB-антителам, раз-вивается ВППБ. При последующих беременностях риск этой патологии возрастает до 17-18% [35][36][37].…”
unclassified